Psychometric Properties of the Verbal Affective Memory Test-26 and Evaluation of Affective Biases in Major Depressive Disorder - Hjordt, Liv V.; Ozenne, Brice; Armand, Sophia; Dam, Vibeke H.; Jensen, Christian G.; Köhler-Forsberg, Kristin; Knudsen, Gitte M.; Stenbæk, Dea S. (Frontiers in Psychology, 2020)
We developed the Verbal Affective Memory Test-26 (VAMT-26), a computerized test to assess ver-bal memory, as an improvement of the Verbal Affective Memory Test-24 (VAMT-24). Here, we psychometrically evaluate the VAMT-26 in 182 healthy controls, examine 1-months test-retest stabil-ity in 48 healthy controls, and examine whether 87 antidepressant-free patients diagnosed with Major Depressive Disorder (MDD) tested with VAMT-26 differed in affective memory biases from 335 healthy controls tested with VAMT24/26. We also examine whether affective memory biases are as-sociated with depressive symptoms across the patients and healthy controls. VAMT-26 showed good psychometric properties. Age, sex, and IQ but not education influenced VAMT-26 scores. VAMT-26 scores converged satisfactorily with scores on a test associated with non-affective verbal memory. Test-retest analyses showed a learning effect and a r≥.0.8, corresponding to a typical variation of 10% in recalled words from first to second test. Patients tended to remember more negative words relative to positive words compared to healthy controls at borderline significance (p=0.06) and affective memory biases were negatively associated with depressive symptoms across the two groups at bor-derline significance (p=0.07), however the effect sizes were small. Future studies are needed to ad-dress whether VAMT-26 can be used to distinguish between depression subtypes in patients with MDD. As a verbal memory test VAMT-26 is a well validated neuropsychological test and we rec-ommend it to be used in Danish and international studies on affective memory.